OPTIMALISASI DAN PENAMBAHAN FITUR APLIKASI E-COMMERCE MITRAKU UNTUK MENINGKATKAN KINERJA DAN KEAMANAN APLIKASI - Putra, I Putu Krisnawan; Supriana, I Wayan; Giri, Gst. Ayu Vida Mastrika (Jurnal Pengabdian Informatika, 2026)
This study focuses on optimizing and enhancing the Mitraku e-commerce application to improve its performance and security. The methodology used is Scrum, which enables the gradual and collaborative development of features. Several security features implemented include password strength indicators and masked icons to enhance user data protection. Additionally, bug fixes for the pagination feature and expanded front-end code testing coverage were implemented to minimize errors and improve application stability and responsiveness. The results of this study indicate that the Scrum methodology is effective for developing the Mitraku e-commerce project, particularly in feature addition, bug fixing, and expanding code testing coverage.